A GSA-based adaptive fuzzy PID-controller for an active suspension system. Issue 6 (1st August 2016) - Chao, Chun-Tang; Liu, Ming-Tang; Chiou, Juing-Shian; Huang, Yi-Jung; Wang, Chi-Jo
Abstract : Purpose: – The purpose of this paper is to propose a novel design for determining the optimal hybrid fuzzy PID-controller of an active automobile suspension system, employing the gravitational search algorithm (GSA). Design/methodology/approach: – The hybrid fuzzy PID-controller structure is an improvement to fuzzy PID-controller by incorporating a fast learning PID-controller. Findings: – The GSA can adjust the parameters of the PID-controller to achieve the optimal performance. Research limitations/implications: – The GSA may have the advantage of quick convergence, but the required computation may be intensive. Practical implications: – The simulation results demonstrate the effectiveness of the proposed approach on active automobile suspension system. Originality/value: – In order to demonstrate the theoretical guarantee of the proposed method, comparisons with particle swarm optimization or other methods has also been carried out.